Ensuring Maximum Stability Degree in the Systems with Interval Parameters; Applied Mechanics and Materials; Vol. 752-753 - Gaivoronsky (Gayvoronsky) S. A. Sergey Anatolievich (Automation, Robotics and Control, 2015)
Title screen